The Effect of Specific Strength Training on Throwing Velocity in Overarm Throwing: A Systematic Review - Andrea Bao Fredriksen; Roland van den Tillaar (SpringerOpen, 2024)
Abstract Background Throwing velocity is an important research topic in sports science, and it is an essential performance variable for athletes in overarm-throwing sports like baseball, team handball, water polo, softball, and cricket. The aim of the present review was to investigate the effect of specific strength training on throwing velocity for overarm throws. Methods The literature was analysed using the Preferred Reporting Items for Systematic reviews and Meta-analyses, searching in SPORTDiscus and MEDLINE. Seventeen studies were included in this review, and the training studies were divided into four categories: (a) overweight and underweight balls, (b) forearm loading, (c) pulley device training, and (d) strength training with a resistance band. Results All strength training studies with resistance band and the forearm loading categories increased the throwing velocity, varying from 3.7 to 26%. However, only half of these studies found that training was associated with a significantly higher increase versus the control group. Findings were inconsistent in other categories. Conclusion Based on the findings of the present review, no clear conclusion can be made on which of the specific strength training methods is best for increasing throwing velocity. However, some recommendations can be offered. Firstly, the throwing training period should be long enough (≥ 6 weeks) with a high enough workload. Throwing training with a resistance band increases throwing velocity significantly for junior and less experienced overarm-throwing athletes. Furthermore, throwing with underweighted balls of similar size will ensure a positive effect on throwing velocity. Also, throwing training with combined over- and underweighted balls can be used if the overweighted balls are carefully selected to ensure there is no negative impact on throwing kinematics and injuries. For the other categories, the results were conflicting. Furthermore, due to the low number of studies in the pulley device and forearm loading categories, more studies should be conducted to investigate their effects on throwing velocity.